2022
DOI: 10.3390/jrfm15040159
|View full text |Cite
|
Sign up to set email alerts
|

Homebuyer Purchase Decisions: Are They Anchoring to Appraisal Values or Market Prices?

Abstract: Price discovery is an important research topic in real estate due to the heterogeneous nature of housing attributes and relatively thin trading activities compared to other assets. In Commonwealth countries, including New Zealand, governments usually conduct periodic appraisals for the purpose of collecting rates and levies. Such official appraisal values of properties, also known as capital values (CVs), are considered a price anchor for market participants in their negotiation processes. Real estate agents o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…The results obtained are difficult to compare directly with other studies, as such attempts have rarely been made to date. However, these results confirm the conclusions presented in the work in papers addressing the price anchoring effect (Leung & Tsang 2013;Shie, 2019;Cheung et al, 2022;Kokot, 2023). This effect occurs and significantly improves the predictive quality of price models.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results obtained are difficult to compare directly with other studies, as such attempts have rarely been made to date. However, these results confirm the conclusions presented in the work in papers addressing the price anchoring effect (Leung & Tsang 2013;Shie, 2019;Cheung et al, 2022;Kokot, 2023). This effect occurs and significantly improves the predictive quality of price models.…”
Section: Discussionsupporting
confidence: 89%
“…When sellers have periodic profit and loss preferences or when buyers attach value to historical housing prices, changes in the prices of real estate are predictable (Leung & Tsang, 2013). On the other hand, a paper (Cheung, et. al., 2022) used property values set by periodic valuations for tax purposes as anchors, proving the existence of a price anchoring effect in the secondary housing market.…”
Section: Real Estate Managementmentioning
confidence: 99%
“…8 To some extent, this study is limited by using appraisal values of properties because they are valuers' estimates of 'the most likely selling price [of the properties] at the date of valuation' (Auckland Council, 2021b) and are only updated once every three years (more information is provided in the Appendix). The advantages of using appraised values include a strong bidirectional association with markettransacted prices (Cheung et al, 2022) and an avoidance of the idiosyncrasies of individual trades. A second limitation of this study is the impact of the pandemic on housing markets and appraisals.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the appraisal value can be regarded as trustworthy information reflecting the property value. Even though Auckland Council states that the revaluation is not intended for marketing or sales purposes, research conducted by Cheung et al (2022) found that market participants use the Capital Value as a price anchor in the price discovery process. Rating valuations consist of three components: Capital Value, Land Value and Improvement Value. Capital Value is the sum of the Land Value and the Improvement Value.…”
Section: Figure B1mentioning
confidence: 99%